KEPENTINGAN KANADA MEMBERI BANTUAN KE INDONESIA MELALUI TRADE PRIVATE SECTOR ASSISTANCE (TPSA) PROJECT - Rachel Yosdelina; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is a study of international political economy analysis  on development cooperation between Canada and Indonesia which has been going on for a long time. However, in 2015 a Canadian-Indonesian collaborative project emphasized the role of Indonesian SMEs in gender equality. This project is called the Trade Private Sector Assistance (TPSA) Project, which is Canada's provision of foreign aid to Indonesia. So, this research was conducted to see Canada's background in assisting Indonesia in the form of the TPSA Project and what was produced and achieved from the provision of foreign aid.This study uses the perspective of liberalism, foreign aid theory, the concept of national interest and the level of analysis of the nation state. The research method that is used is the qualitative research that is explanative by collecting data from the official website of the TPSA Project, the website of the Canadian Ministry of Foreign Affairs (Global Affairs Canada) and the Ministry of Trade, Transnational Journal, Journal of Development Economics, Journal of World Affairs and Introduction to International Relations Studies, Foreign Aid: Diplomacy, Development, Domestic Politics and International Political Economy and Development books.The results of this study are that Canada has economic and political benefits in Indonesia, namely strengthening Canada's contribution towards the Sustainable Development Goals (SDGs), Indonesian SMEs can meet Canadian import standards for products exported by Indonesian SMEs and expand the Canadian market in Indonesia, thereby increasing Canada's trade with Indonesia and Canada spread its values in the form of aspects of gender equality in Indonesian SMEs and a positive image of Canada in Indonesia and the world.  Keywords        : National Interest, Foreign Aid, Private Sector Development, Gender Equality, TPSA Project, Canada and Indonesia.